Prospective, multicenter study of postoperative deep-vein thrombosis in patients with haemophilia undergoing major orthopaedic surgery - Buckner, Tyler W.; Leavitt, Andrew D.; Ragni, Margaret; Kempton, Christine L.; Eyster, M. Elaine; Cuker, Adam; Lentz, Steven R.; Ducore, Jonathan; Leissinger, Cindy; Wang, Mike; Key, Nigel S. (Thrombosis and Haemostasis, 2016)
Perioperative clotting factor replacement is administered to reverse the inherent haemostatic defect in persons with haemophilia (PWH), potentially increasing their risk for developing venous thromboembolism (VTE) postoperatively. It was our objective to determine the prevalence of VTE in PWH undergoing total hip or knee arthroplasty (THA, TKA). Patients with haemophilia A or B who underwent THA or TKA were enrolled in this prospective, multicentre observational cohort study. Lower extremity venous duplex ultrasound was performed prior to surgery and 4–6 weeks after surgery. Eleven centres enrolled 51 subjects, 46 of whom completed the study. Six subjects (13.0 %) were treated with bypass agents perioperatively; the remaining 40 subjects received factor VIII or IX replacement. Intermittent pneumatic compression devices were utilised postoperatively in 23 subjects (50 %), and four subjects (8.7 %) also received low-molecular-weight heparin prophylaxis. One subject (2.2 %) with moderate haemophilia A was diagnosed with symptomatic distal deep-vein thrombosis (DVT) on day 6 following TKA. One subject (2.2 %) with severe haemophilia A was diagnosed with pulmonary embolism on day 9 following bilateral TKA. No subjects had asymptomatic DVT. Eighteen subjects (39.1 %) had major bleeding, and three subjects (6.5 %) experienced minor bleeding. The observed prevalence of ultrasound-detectable, asymptomatic DVT in PWH following TKA or THA in this study was low, but the incidence of symptomatic VTE (4.3 %, 95 % CI, 0.5–14.8 %) appeared similar to the estimated incidence in the general population without thromboprophylaxis.
Keywords: Haemophilia therapy; orthopaedics; venous thrombosis